Adsorption of Biologically Active Compounds from Aqueous Solutions on to Commercial Unmodified Activated Carbons. Part V. The Mechanism of the Physical and Chemical Adsorption of Phenol - Artur P. Terzyk (Adsorption Science & Technology)
The study presented described the influence of temperature as well as pH on phenol adsorption (and the adsorption kinetics) on to three unmodified commercial carbons. The first section of the paper provided a description of the characterization of the carbons employing the most sophisticated method of carbon porosity characterization at present available, i.e. the method of Do and co-workers (the ND method). It was then shown that the ND method leads to the same results as the Density Functional Theory (DFT). The TPD results for D43/1, WD and AHD carbons were then presented and discussed with deconvolution of the peaks being performed. The results obtained together with those already published led to an assignment of the chemical structures of the surface functionalities for all the carbons studied. Thermogravimetric analysis of phenol adsorption indicated that the number of molecules bonded chemically was small. Adsorption of phenol under acidic conditions (pH 1.5) was lower than at neutral pH for all the carbons studied. A description of the corresponding isotherms applying adsorbability, quasi-Freundlich and DA models, together with enthalpy measurements, led to a mechanism for the adsorption of phenol at both pH values. This mechanism was further confirmed by some empirical correlations and by a comparison with data obtained recently for modified chemically carbons. Some new correlations between the properties of the carbon surface and the constants characterizing the process of phenol adsorption suggested recently were extended from data which had been measured for six carbons initially. Analysis of the average hysteresis on the adsorption/desorption isotherms, as well as a comparison of phenol adsorption under oxic and anoxic conditions, led to a mechanism for the irreversible adsorption of phenol. It was suggested that such irreversibility resulted from two effects: the creation of strong complexes between the phenol molecule and surface carbonyl and lactone groups, as well as polymerization. The latter effect arose from the ability of carbon to adsorb oxygen from solution and form superoxo ions. A mechanism for such polymerization was proposed. Finally, the kinetics of the process were considered. The diffusion coefficients were calculated from an application of the analytical solution of Fick's law of diffusion for adsorption in cylindrical particles. It was shown that phenol diffusion occurs via a mixed process involving the carbon surface and pores. The diffusion energy obtained was correlated with the values for the physicochemical parameters of the carbons studied. It was concluded that the mechanism of phenol adsorption was determined not only by so-called ‘π–π interactions’ and ‘donor–acceptor complex’ formation, but also by a ‘solvent effect’ balancing the influence of the two above-mentioned factors, this solvent effect being strongly dependent on the temperature.